Socioeconomic Factors and Outcomes in Higher Education : A Multivariate Analysis - Carlos Felipe Rodríguez Hernández (Universidad externado de Colombia, 2016)
In the Colombian case, it is very common to associate academic performance with the students' socioeconomic conditions. A generalized and bivariate interpretation of this relationship could imply that only students from a high socioeconomic class would perform satisfactorily and that all students from a low socioeconomic class would perform poorly. If this is the case, then the educational system could be increasing the gap between social classes instead of making it smaller. Therefore, it seems important to examine the way in which some socioeconomic factors are related to the students' academic performance in Colombia. Consequently, Socioeconomic Factors and Outcomes in Higher Education: a Multivariate Analysis, explores the relationship between the results in standardized tests and socioeconomic variables in a cohort of Colombian students.